Long-term outcomes after proton therapy, with concurrent chemotherapy, for stage II–III inoperable non-small cell lung cancer. Issue 3 (June 2015) - Nguyen, Quynh-Nhu; Ly, Ngoc Bui; Komaki, Ritsuko; Levy, Lawrence B.; Gomez, Daniel R.; Chang, Joe Y.; Allen, Pamela K.; Mehran, Reza J.; Lu, Charles; Gillin, Michael; Liao, Zhongxing; Cox, James D.
Abstract Purpose We report long-term disease control, survival, and toxicity for patients with locally advanced non-small cell lung cancer prospectively treated with concurrent proton therapy and chemotherapy on a nonrandomized case-only observational study. Methods All patients received passive-scatter proton therapy, planned with 4D-CT–based simulation; all received proton therapy concurrent with weekly chemotherapy. Endpoints were local and distant control, disease-free survival (DFS), and overall survival (OS). Results The 134 patients (21 stage II, 113 stage III; median age 69 years) had a median gross tumor volume (GTV) of 70 cm3 (range, 5–753 cm3); 77 patients (57%) received 74 Gy(RBE), and 57 (42%) received 60–72 Gy(RBE) (range, 60–74.1 Gy(RBE)). At a median follow-up time of 4.7 years, median OS times were 40.4 months (stage II) and 30.4 months (stage III). Five-year DFS rates were 17.3% (stage II) and 18.0% (stage III). OS, DFS, and local and distant control rates at 5 years did not differ by disease stage. Age and GTV were related to OS and DFS. Toxicity was tolerable, with 1 grade 4 esophagitis and 16 grade 3 events (2 pneumonitis, 6 esophagitis, 8 dermatitis). Conclusion This report of outcomes after proton therapy for 134 patients indicated that this regimen produced excellent OS with tolerable toxicity.